Child public health - Blair, Mitch (Oxford : Oxford University Press, 2010)
This text focuses on a public health approach to the health and sickness of children and young people - comprising about a quarter of the population. It explores the state of health of our children, the historical roots of the specialty and the relation between early health and later adult health.
Previous ed.: 2003.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Children -- Health and hygiene -- Great Britain; Public health -- Great Britain; Child health services -- Great Britain